2021
DOI: 10.1177/01454455211016819
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Lower-Order Anxiety Sensitivity Facets and PTSD Symptomatology among Trauma-Exposed Firefighters

Abstract: Firefighters are chronically exposed to potentially traumatic events, augmenting their risk of developing posttraumatic stress disorder (PTSD). The current study aimed to examine the incremental associations of lower-order dimensions of anxiety sensitivity (AS), examined concurrently, and PTSD symptom severity among a sample of trauma-exposed firefighters. We hypothesized that AS physical and cognitive concerns would be strongly associated with all PTSD symptom clusters and overall symptom severity, after cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…However, here we did not find any effect of anxiety sensitivity or the cognitive concerns sub-factor upon the avoidance symptom cluster. Notably, similar results were seen in Kreminski et al (2021), as well as previous research in both military and general populations (Lebeaut et al, 2021; Raines et al, 2017b) suggesting the results of this current study are not idiosyncratic to ADF veterans. The reason for this lack of empirical association between anxiety sensitivity and avoidance symptoms is unclear.…”
Section: Discussionsupporting
confidence: 91%
“…However, here we did not find any effect of anxiety sensitivity or the cognitive concerns sub-factor upon the avoidance symptom cluster. Notably, similar results were seen in Kreminski et al (2021), as well as previous research in both military and general populations (Lebeaut et al, 2021; Raines et al, 2017b) suggesting the results of this current study are not idiosyncratic to ADF veterans. The reason for this lack of empirical association between anxiety sensitivity and avoidance symptoms is unclear.…”
Section: Discussionsupporting
confidence: 91%
“…There is a large body of work on anxiety sensitivity, trauma, and PTSD among largely non-Latinx White persons (Bakhshaie et al, 2016; Brandt et al, 2015; Lebeaut et al, 2022; Raines et al, 2022; Zvolensky et al, 2020). This research has been influential in showcasing that individual differences in anxiety sensitivity are consistently related to poor trauma-related health (Raines et al, 2017b) and may represent a mechanism linking other vulnerability factors to more severe mental health in general (Raines et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that fear of anxious arousal may intensify emotional reactions (e.g., psychological and physiological) to trauma cues, thereby leading to increased PTSD symptom severity (Taylor, 2003). Notably, AS exhibits cross-sectional (Lebeaut et al, 2022; Olatunji & Wolitzky-Taylor, 2009) and longitudinal associations (Boffa et al, 2016; G. N. Marshall et al, 2010) with PTSD symptoms in both unselected community (Bardeen & Fergus, 2016) and clinical veteran samples (Raines et al, 2017), such that higher AS is associated with greater PTSD symptom severity.…”
mentioning
confidence: 99%
“…For example, Boffa et al (2016) found that higher levels of AS prior to a school shooting predicted greater PTSD symptoms after the shooting. When examining subdomain associations, AS cognitive, as compared to AS physical and AS social, exhibits the most robust association with PTSD symptom severity (Lebeaut et al, 2022; Raines et al, 2017). Cognitive concerns, versus physical or social, may be particularly relevant as PTSD is characterized by maladaptive trauma-related cognitions.…”
mentioning
confidence: 99%